PENGARUH JENIS KAYU DAN KOMPOSISI PEREKAT UREA FORMALDEHIDATERHADAP KETEGUHAN REKAT KAYU LAPIS BEBERAPA JENIS KAYU HUTAN TANAMAN INDUSTRI - Suwandi Kliwon; M I lskandar; Paribroto Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
A glue shear test was conducted using plywood panel, made from three wood species namely pine (Pinus merkusii Yung et de Vr.), Eucalyptus alba and Eucalyptus deglupta from West Java. The bolts were rotary peeled into veneer of 1.5 mm thick.The veneer sheets were glue with urea formaldehyde resin in combination with meranti and kapur veneers. Each plywood sample thus consisted of three layer veneer and meranti merah (red meranti) and kapur (Dryobalanops oramatica Gaert) as face and back veneers.The bonding strength (glue shear strength) of each plywood type were then tested according to the Indonesian and Japaneess standard. The result indicates that there were significant differences between wood species and variation of extender composition according to the Indonesian standard and only percentage of extenders indicated significant difference using Japaneess standard. Percentage 10% extender was the best bonding strength of plywood comprising with the others.